Modeling of the Complex Modulus of Asphalt Mastic with Biochar Filler Based on the Homogenization and Random Aggregate Distribution Methods - Yushuai Wu; Peng Cao; Feiting Shi; Ketong Liu; Xuhao Wang; Zhen Leng; Zhifei Tan; Changjun Zhou (Advances in Materials Science and Engineering)
The disposal of agricultural straw has been a severe environmental concern in China and many other countries. In this study, the complex modulus of using biochar converted from straw as an alternative mineral filler in asphalt mastic was investigated through both laboratory tests and modeling. The experimental results indicated that the biochar can provide asphalt mastic higher stiffness than the conventional granite mineral filler. It was believed that the special porous structure of biochar providing a thicker coating layer of mineral filler increases the stiffness modulus of asphalt mastic. To consider this factor into the micromechanical model, a modified generalized self-consistent model (MGSCM) with a coating layer was proposed. Besides, the finite element (FE) microstructural model with a coating layer generated by random aggregate distribution method was used to numerically evaluate the effect of the coating layer on the complex modulus of asphalt mastics. The predicted results indicated that the generalized self-consistent model (MGSCM) with a coating layer is an efficient and accurate model for predicting the complex modulus of asphalt mastics. Moreover, the FE modeling proved that the coating layer can significantly improve the complex modulus of asphalt mastics. Therefore, the experiments and modeling carried out in this study provided insight for biochar applications to improve the performance of asphalt mixtures.